2011
DOI: 10.1371/journal.pone.0017757
|View full text |Cite
|
Sign up to set email alerts
|

Monocrotophos Induced Apoptosis in PC12 Cells: Role of Xenobiotic Metabolizing Cytochrome P450s

Abstract: Monocrotophos (MCP) is a widely used organophosphate (OP) pesticide. We studied apoptotic changes and their correlation with expression of selected cytochrome P450s (CYPs) in PC12 cells exposed to MCP. A significant induction in reactive oxygen species (ROS) and decrease in glutathione (GSH) levels were observed in cells exposed to MCP. Following the exposure of PC12 cells to MCP (10−5 M), the levels of protein and mRNA expressions of caspase-3/9, Bax, Bcl2, P53, P21, GSTP1-1 were significantly upregulated, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…Results of Kashyap et al (2011) indicated that Fish Physiol Biochem induced expression of CYPs might have up-regulated the production of ROS in cells after monocrotophos exposure. The antioxidant enzymes, on the other hand, play an important role in scavenging the overproduced ROS in tissues, but whether monocrotophos can interfere with the scavenging of ROS is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of Kashyap et al (2011) indicated that Fish Physiol Biochem induced expression of CYPs might have up-regulated the production of ROS in cells after monocrotophos exposure. The antioxidant enzymes, on the other hand, play an important role in scavenging the overproduced ROS in tissues, but whether monocrotophos can interfere with the scavenging of ROS is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (2008) reported that chlorpyrifos increases the levels of DNA damage and lipid peroxidation and decreases activities of antioxidant enzymes superoxide dismutase (SOD), catalase, and glutathione peroxidase (GSH-Px) in the retina of mice, suggesting that inhibition of antioxidant enzyme activities may increase the level of ROS and further lead to the damage of DNA. Recently, Kashyap et al (2011) found that exposure of 10 -5 M monocrotophos increased the level of ROS in PC12 cells by elevating the mRNA expressions of CYP1A1/1A2, 2B1/2B2, 2E1 enzymes; however, whether the DNA damage induced by this pesticide is associated with alterations in the antioxidant system and accumulation of ROS is still equivocal. Therefore, to investigate the types of DNA damage induced by monocrotophos, different versions of the comet assay were applied in peripheral erythrocytes of goldfish (Carassius auratus) exposed to 0.01, 0.10, and 1.00 mg/L of this pesticide: The alkaline (pH [ 13), pH 12.1, and neutral (pH 8.2-8.5) comet assays were used to identify the global DNA damage (includes DSB, SSB, and ALS), DSB and SSB, and DSB, respectively; and the alkaline comet assay combined with endonuclease III (Endo III) or formamidopyrimidine DNA glycosylase (FPG) and with fluorescence in situ hybridization (FISH) was used to detect oxidative damage in DNA bases and telomeric DNA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Differential susceptibility to chlorpyrifos in these two cell lines may be explained, at least in part, by the fact that the transcription factor HNF1 (hepatic nuclear factor 1) is expressed ten times more in JAR than in JEG-3 cells , with this transcription factor playing an important role in CYP regulation. Although the involvement of CYPs in OP-induced apoptosis in neuronal cells has been previously reported (Kashyap et al, 2011), it is still not clear whether OP metabolism by CYPs and the induction of oxidative stress are implicated in trophoblast cell death.…”
Section: Proliferation/death Imbalancementioning
confidence: 98%
“…Apoptotic nuclei were assessed by fluorescence microscopy using the Zeiss Axioimager, and images were captured using the Isis software (Metasystems,Altlussheim, Germany). PC12 cells exposed to camptothecin at a concentration of 3 lg/ml (Sigma-Aldrich C-9911) for 6 h (Kashyap et al 2011) were used as a positive control.…”
Section: Terminal Deoxynucleotidyl Transferase Dutp Nick End Labelingmentioning
confidence: 99%